Bayesian data analysis in ecology using linear models with R, bugs, and Stan : including comparisons to frequentist statistics /: including comparisons to frequentist statistics. (2015) - Korner-Nievergelt, Fränzi; Roth, Tobias; von Felten, Stefanie; Guélat, Jérôme; Almasi, Bettina; Korner-Nievergelt, Pius
No abstract available